Analisa Kelayakan Peralatan Pompa Di Permukaan Dan Dyna Cards Terhadap Penurunan Produksi Harian Di Sumur “BD” Lapangan “SEI” - Aly Rasyid; Eko Prastio; Ode Rifaldi (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2023)
In an effort to lift oil and gas from a subsurface reservoir, companies engaged in oil and gas must carry out production operations. The production operation itself aims to make oil and gas produced or lifted to the surface. However, the problems faced to carry out maintenance in this production operation are not small and can even be categorized as a very expensive job. In order to reduce the budget of production operations there needs to be efficien by doing good maintenance and observation. One aspect that needs to be considered in the maintenance of production operations is the appropriateness of the equipment. This determination of feasibility greatly influences the cost of production operations due to maintenance, and observation is one of the most expensive part of production operations. Therefore it is necessary to have the right assessment and observation before deciding that the pump equipment used is suitable and efficient. In this study aims to evaluate the feasibility of surface and downhole pump equipment related to lower pump efficency. It is expected to be used as suggestions and consideration to evaluate the performance and safest downhole pump equipment.